2021
DOI: 10.3390/jcm10184185
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants in Patients with Obesity and Atrial Fibrillation: Position Paper of Italian National Association of Hospital Cardiologists (ANMCO)

Abstract: The use of the direct oral anticoagulants dabigatran, rivaroxaban, apixaban and edoxaban (DOACs) offers some major advantages over warfarin and other vitamin K antagonists (VKAs). One advantage is the possibility to use a fixed dose in normal-weight patients, overweight patients and patients with obesity. However, the “one size fits all” strategy raised a concern regarding the possibility to undertreat patients with a high body mass index. No randomized controlled trials (RCTs) have ever compared VKAs and DOAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Although epidemiological studies have shown that the presence of obesity is associated with numerous diseases, as reported in Table 5 , for some specific diseases, a better outcome has been reported in those overweight or with first-degree obesity (BMI ≥ 30 kg/m 2 and < 35 kg/m 2 ), compared to those who had a BMI < 25 kg/m 2 [ 137 ]. Since the first identification of this counterintuitive finding, numerous similar studies have been published in different fields, such as cardiovascular diseases [ 138 ], cancer [ 139 ], diabetes [ 140 ], respiratory diseases [ 141 ] and in other clinical contexts [ 142 ]. A recent large cohort study including patients with stable coronary heart disease has found a U‐shaped relationship between BMI and cardiovascular outcomes, with the lowest cardiovascular risk in patients with a BMI of 27 kg/m 2 , which are usually classified as overweight patients [ 143 ].…”
Section: Obesity Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Although epidemiological studies have shown that the presence of obesity is associated with numerous diseases, as reported in Table 5 , for some specific diseases, a better outcome has been reported in those overweight or with first-degree obesity (BMI ≥ 30 kg/m 2 and < 35 kg/m 2 ), compared to those who had a BMI < 25 kg/m 2 [ 137 ]. Since the first identification of this counterintuitive finding, numerous similar studies have been published in different fields, such as cardiovascular diseases [ 138 ], cancer [ 139 ], diabetes [ 140 ], respiratory diseases [ 141 ] and in other clinical contexts [ 142 ]. A recent large cohort study including patients with stable coronary heart disease has found a U‐shaped relationship between BMI and cardiovascular outcomes, with the lowest cardiovascular risk in patients with a BMI of 27 kg/m 2 , which are usually classified as overweight patients [ 143 ].…”
Section: Obesity Paradoxmentioning
confidence: 99%
“…The increase in epicardial fat, along with the increase in the production of inflammatory and profibrotic mediators, which have both endocrine and paracrine effects, may explain the higher risk of AF among patients with obesity [ 180 ]. Of note obesity may also affect anticoagulant drug pharmacokinetics and pharmacodynamics and in patients with severe obesity the anticoagulant treatment must be individualized [ 142 ].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Nevertheless, in severely obese patients, it has been postulated to consider the assessment of DOACs’ plasma levels [ 18 , 157 ]. Due to the higher reliability and the association with clinical outcomes, it is generally recommended to measure trough levels of the DOAC, although whether to evaluate the trough or peak plasma levels is currently a subject of ongoing research [ 18 ].…”
Section: Doacs In Under and Overweight Patientsmentioning
confidence: 99%
“…The effects of BMI on DOAC are limited. Thus, they may be considered generally safe and effective across weight classes [ 99 ]. A systematic review and meta-analysis suggests that DOAC has similar efficacy and safety in preventing recurrent thromboembolic events in patients with severe obesity [ 100 ].…”
Section: Obesity and Thrombosis: Treatmentmentioning
confidence: 99%